Pengembangan Literasi Menulis Siswa MIS Darul Ulum Genengan: Pelatihan Penulisan Kalimat Efektif dan Penggunaan Tanda Baca - Adin Fauzi; M Iqbal Baihaqi; Sinta Yuliani (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
This community service aims to develop students' writing literacy in the form of training. The main focus of this community service is to train students to write effective sentences and apply punctuations. This training involved 15 grade VI students of MIS Darul Ulum Genengan who had taken the Minimum Competency Assessment (AKM). They were selected as training participants to follow up on the results of the AKM. The training was held for 6 meetings in the period from August 1–31, 2022. The training activities include: pretest (writing text); vocabulary identification; sentence analysis; punctuation analysis; vocabulary, sentence, and punctuation exercises; and posttest (writing text). These activities were carried out in groups and individually by applying attractive learning strategies and media. After participating in the training, 80% of students were able to reach a proficient level in writing. This result far exceeds the pre-training achievement; that is, 73% of students were only able to reach the basic level. With these results, it is highly recommended for the school to intensify literacy activities, especially writing. Those who are talented can continue to hone their skills, and those who still need special intervention can continue to develop their abilities.